Arsenic Precipitation in Heavily Arsenic‐Doped Czochralski Silicon. Issue 3 (14th December 2022) - Wu, Defan; Zhao, Tong; Ye, Bin; Liang, Xingbo; Chen, Hao; Nie, Qunlin; Tian, Daxi; Yang, Deren; Ma, Xiangyang
Abstract : Heavily arsenic‐doped Czochralski (HAs‐CZ) silicon is an important substrate material for manufacturing power electronic devices. The arsenic impurities may be in a supersaturated status in a certain temperature range during the HAs‐CZ silicon crystal growth or the device fabrication. Then, whether and how the arsenic impurities can precipitate in HAs‐CZ silicon is an intriguing and practically significant issue that has never been addressed. Herein, it is first found that arsenic precipitation can occur in HAs‐CZ silicon when subjected to appropriately prolonged anneals at 550–950 °C. The resulting second‐phase precipitates are confirmed to be of orthorhombic SiAs phase, with the lattice parameters of a  = 7.12 Å, b  = 9.11 Å, and c  = 9.00 Å, through systematic transmission electron microscopy characterizations. Moreover, it is discovered that the presence of vacancies/interstitial silicon atoms in HAs‐CZ silicon promotes/inhibits arsenic precipitation. Abstract : It is first found that arsenic precipitation can occur in HAs‐CZ silicon when subjected to appropriately prolonged anneals at 550–950 °C. The resulting second‐phase precipitates are confirmed as orthorhombic SiAs phase, with the lattice parameters of a  = 7.12 Å, b  = 9.11 Å, and c  = 9.00 Å. The presence of vacancies/interstitial silicon atoms in silicon promotes/inhibits arsenic precipitation.